An Observation of Very Low Frequency (VLF) Electromagnetic Waves Generated by Lightning Strikes via RockSat-X - McMahon, Breonna; Boissonnas, Ariane; Lee, Nathaniel; Becher, Max; Shannon, Thomas; Hernandez, Michael; Rice, Jordan; Bradshaw, Stephanie; McCulloch, Adam (Proceedings of the Wisconsin Space Conference, 2017)
In an attempt to observe how very low frequency (VLF) signals from lightning discharges vary as a function of altitude, a sounding rocket payload was built and launched via the Colorado Space Grant Consortium’s RockSat-X program. The main components of the payload consisted of three magnetic field antennas, two pairs of electric field plate antennas, an amplification and filtration circuit board, and two microSD cards interfaced with high performance multi-core microcontrollers for data storage. Despite a flight anomaly preventing the retrieval of the stored data, low resolution telemetry data from flight shows the expected presence power line interference.